The Impact of Earnings Announcements on Share Prices: Evidence from US Stock Exchange - Jabrayilova, Nigar (2016)
The present paper aims to examine the relationship between the earnings announcements and share prices in US stock markets for the period January 1, 1012 – December 31, 2015. For this purpose, short-horizon event study methodology has been employed for 480 events of thirty Dow Jones Industrial Average (DJIA) Index companies. Consensus analysts’ estimates have been used as a proxy of earnings expectations. Earnings surprises have been classified into three groups according to its information content: good news, bad news, and no news. Cumulative average abnormal returns have been calculated with the market model in to understand the share price reaction to earnings announcements. The findings suggested that overall there are no significant abnormal returns in the US market. Stock prices react to earnings announcements sharply during the event day and significance of the abnormal returns decrease throughout the event window. The results show that investors over-react to bad news than other types of new information. The test results suggested that post-earnings-announcement drift does not exist and share prices digest the new information over the event window. As a result, earnings announcements do not have a long-term effect on share prices and US stock markets are efficient in semi-strong form.